Shari'ah court and the role of muftīs in the Nigerian judiciary: mission on reviving the lost glory of its past - Chiroma, Magaji; Arifin, Mahamad; Ansari, Abdul Haseeb; Abdullah, Mohamad Asmadi (2014)
Shari'ah Court and the Role of Muftīs in the Nigerian Judiciary: Mission on Reviving the Lost Glory of its Past Magaji Chiroma a*, Mahamad Bin Arifinb, Abdul Haseeb Ansaric, Mohammad Asmadi Abdullahd a Ph.D. Candidate, AIKOL, International Islamic University Malaysia; Department of Sharia Law, Faculty of Law, University of Maiduguri, Nigeria b Department of Islamic Law, AIKOL, International Islamic University Malaysia, Kuala Lumpur, Malaysia c Department of Civil Law, AIKOL, International Islamic University Malaysia, Kuala Lumpur, Malaysia d Department of Islamic Law, AIKOL, International Islamic University Malaysia, Kuala Lumpur, Malaysia *Corresponding Author. E-mail: magajichiroma@gmail.com Abstract Islamic institutions in Nigeria have been in existence since the advent of Islam in the country. While courts were established in order to adjudicate between disputant parties, muftis were also used as assessors (as part of the court officials) responsible for assisting the courts in dispensation of Shari‘ah justice. When the colonial administrators came, they introduced their legal system to the colonies, which led to a gradual wipe away of some aspects of the Islamic legal system (including the courts and fatwa institutions). The doctrine of the tripartite tests (i.e the repugnancy test, incompatibility test and public policy test) was injected into the country’s legal system to the extent that the full and hitherto application of Islamic law was modified. Muslims are left only with matters bothering on the civil causes and personal matters. Islamic scholars such as muftis became functus officio in the Shari‘ah Courts. In view of this, the paper looks at the possibility of reviving the past glory of the role of a mufti in the Nigerian judicial system. Thus, it sets out some modalities on how fatwa can be streamlined in achieving this objective. One of such modalities is to institutionalize fatwa in the country. Keywords: Shari„ah Court, Role of a muftī, Nigeria, Judiciary